Why Wait? The Ethics of Disclosing HIV Screening Results - Zain Aryanpour MD; Skye Opsteen BS; Olivia T. Van Gerwen MD, MPH; Christina A. Muzny MD, MSPH; Sonya L. Heath MD, MS (SAGE Publishing, 2023)
Counseling patients on their HIV test results is an important part of undergraduate and graduate medical education. However, many trainees and physicians feel ill prepared to counsel patients on potentially distressing results. We present a case involving early disclosure of a false-positive HIV screening test result to a patient and the downstream effects of this premature disclosure. This case highlights the importance of understanding the various HIV testing options available and the importance of education on effectively counseling patients on screening versus confirmatory HIV test results.